Differential Effects of Mindfulness-Based Intervention Programs at Work on Psychological Wellbeing and Work Engagement - Calcagni, Cristián Coo; Salanova, Marisa; Llorens, Susana; Bellosta-Batalla, Miguel; Martínez-Rubio, David; Martínez Borrás, Rosa (Frontiers in Psychology, 2021)
Two different mindfulness-based interventions were deployed in a sample of white-collar workers to explore the differential effects on different facets of mindfulness, dimensions of psychological wellbeing, work engagement, performance, and stress of a participant. A total of 28 participants completed one of the different programs, and their results were compared between groups and against 27 participants randomly allocated to a waiting list control group. Results suggest both mindfulness intervention programs were successful at increasing the levels of psychological wellbeing, work engagement, and performance of the participants, as well as decreasing their levels of stress. Significant differences were found between the two programs in all outcome variables. Results suggest that brief and customized mindfulness interventions at work are as successful as lengthier programs.